Association between HSD11B1 polymorphism and left ventricular mass in families with hypertension. (22nd September 2015) - Rahman, T; Avery, PJ; Mayosi, BM; Watkins, H; Keavney, B
Abstract : Background: The 11β-hydroxysteroid dehydrogenase type 1 ( HSD11B1 ) gene plays an important role in glucocorticoid metabolism. HSD11B1 is a bidirectional enzyme, but it displays oxoreductase activity in intact cells, converting inactive cortisone to cortisol. The reductase activity of HSD11B1 plays an important role in the growth and differentiation of adipose tissue via the activation of glucocorticoids. Increased HSD11B1 activity has been proposed as a mechanism underlying the association between multiple cardiovascular risk factors, whereas inhibition of HSD11B1 has been proposed for the treatment of diabetes and central obesity. Left ventricular mass (LVM) is a significantly heritable trait that is associated with cardiovascular morbidity and mortality independent of hypertension. The genetic factors responsible for differences in LVM within the general population are, as yet, largely unknown. We investigated the contribution of common genetic variants in the HSD11B1 to LVM in a family-based study. Methods: 1425 individuals from 248 white families were analysed. Families were ascertained through a proband with essential hypertension. The proband was required to have had an ambulatory blood pressure monitor (>140 mm Hg mean daytime systolic blood pressure (SBP) and >90 mm Hg mean daytime diastolic blood pressure (DBP)/multiple office SBP >160 mm Hg and DBP >95 mm Hg). Ambulatory blood pressure was recorded in all family members using the A&D TM2421 monitor for 24 h. LVM was measured using both electrocardiography and echocardiography. We genotyped 13 Tag single nucleotide polymorphisms (SNP) on a Sequenom MassArray MALDI-TOF platform that together captured the common genetic variability in the HSD11B1 gene (fig). The LVM was adjusted for covariates including drug treatment, age and gender, by linear regression, and a family-based association analysis was conducted using MERLIN. Results were corrected for multiple comparisons specifying a false discovery rate of 5%. Result: Out of 13 Tag SNP analysed in HSD11B1, one SNP was associated with a difference in LVM measured either by echocardiography or electrocardiography (rs846910 : p = 0.003 for echo LVM; p = 0.03 for ECG LVM; see table). The rarer A allele of rs846910 (frequency 0.052) was associated with lower LVM both in analyses of linear trend and under a dominant model. Conclusion: The HSD11B1 SNP rs846910 was significantly associated with both echocardiographic and electrocardiographic LVM in these families, although the size of the effect was small. This SNP has been associated with hypertension in one previous study, although there was no significant association with blood pressure phenotypes in the present study. rs846910 is located in the first intron of HSD11B1, and its function is as yet unclear. This is the first study to demonstrate an association between the HSD11B1 gene and LVM; future studies will be necessary to determine the mechanism of the effect.